Rituals as portals of transcendence in the lives of older adults - Grudzen, Marita (Journal of religion, spirituality & aging, 2018)
In our present society in the West, we witness significant change and loss on multiple levels for our diverse older population. It is in this context, as well as that of our increased longevity, that I examine the role of ritual in late life transcendence. Are there rituals performed alone or in relationship, in addition to traditional religious rituals, that increase our sense of aliveness, purpose, and are potentially transformational in our later years? Ritual, in this sense, would be a form of connection that is revisited for its whole-making. I affirm the inner Presence, which supports an organic emergence of ritual that is strengthened by the energy and witness of community. This article includes several examples of this person-centered process at different stages in the late life process and among diverse elders. It includes a description of the Croning Ceremony which I co-led with Patricia Thorne at the 2015 International Conference on Spirituality and Ageing. Drawing on our natural environment together with the work and lived experience of anthropologists, gerontologists, ethnogerontologists, Jungian therapists, psychiatrists, psychologists, theologians, ministers, nurses, and family and diverse community members, I seek a holistic perspective on ritual and its role in our transcendence. The article closes with questions that can serve as stepping stones in preparing us to serve as companions and facilitators for our elders.